Conjugated porphyrin oligomers from monomer to hexamer - Taylor, P; Huuskonen, J; Rumbles, G; Aplin, RT; Williams, E; Anderson, H (1998)
A series of conjugated porphyrin oligomers have been prepared and the evolution in their electronic properties is discussed; the crystal structure of the dimer is presented, as well as the MALDI TOF mass spectrum of the hexamer.